Answer:
The solution for -3x + 9 = 5x – 23 is 4
Solution:
From question, given that -3x + 9 = 5x – 23
By moving 5x from right side to left side, we get the above equation as,
-3x – 5x + 9 = – 23
By combining -3x and -5x,
We know that addition of -3x and -5x yields -8x. hence the above equation becomes,
-8x + 9 = -23
By moving 9 from left side to right side, the above equation becomes,
-8x = -23 -9
-8x = -32
Negative sign on both sides cancels out each other.
8x = 32
![x = (32)/(8) = 4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2p1oycrytqmwjcelbz9q5clktwxojaqrac.png)
hence the solution of -3x + 9 = 5x – 23 is 4